A Ti L3, 2 - and K- edge XANES and EXAFS study on Fe3+ - substituted CaCu3Ti4O12. Issue 17 (1st December 2018) - Raval, Pooja Y.; Joshi, Niketa P.; Pansara, Pooja R.; Vasoya, Nimish H.; Kumar, Sudhish; Dolia, Satya Narayan; Modi, Kunal B.; Singhal, Rishi Kumar
Abstract: The electronic structures of stoichiometric, single phase, coarse-grained CaCu3- x Ti4- x Fe2 x O12 ( x = 0.0, 0.1, 0.3, 0.5 and 0.7) polycrystalline ceramics have been investigated using powerful X-ray absorption near-edge structure (XANES) and extended X-ray absorption fine structure (EXAFS) spectroscopic measurements, performed near Ti L 3, 2 and Ti K- edges, registered at 300 K. The absence of pre-edge structures in Ti L 3, 2 – edge are indicative of a departure from octahedral cubic symmetry, while the observed small increase in the intensity of absorption peaks has been attributed to increasing spin-orbital coupling with increasing Fe-content ( x ) in the system. The presence of a pre-edge feature in Ti K - edge spectra confirms the presence of octahedrally coordinated Ti 4+ ions in the system. The EXAFS spectra measured at Ti K - edge indicate the first shell Ti—O bond distances to be nearly 1.56 Å in the sample without Fe. With the increase in the Fe- concentration ( x ), the Ti-O distance shows a slight reduction. The second shell Ti-Ca bond distance comes out to be nearly 2.6 Å which decreases with an increase in the Fe - concentration.